Penggunaan Path Analysis Dalam Analisis Pengaruh Efisiensi Operasional, Tingkat Kecukupan Modal Dan Likuiditas Terhadap Profitabilitas Bank Umum Syariah Di Indonesia Tahun 2011-2014 - Prasetyoningrum, Ari Kristin; Hasanah, Siti Nur (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2016)
This study was to determine the effect of Operating Costs (ROA), level of capital adequacy (CAR), and Liquidity (QR) to Profitability (ROA) at the Islamic Banks in 2011-2014. This study used quantitative research methods. Source of research data are secondary data from the quarterly financial statements of Islamic Banks in 2011 to 2014 were obtained from the website. This study using path analysis because there are two models of the equation (substructure) with IBM SPSS application program. Purposive sampling technique is used to determine number of sample. The sample was seventh quarterly financial statements Islamic Bank (BRI Syariah, Bank Syariah Mandiri, Bank Panin Syariah, BCA Syariah, Bank Mega Syariah, and Maybank Syariah) from 2011 to 2014, each bank was obtained 16 financial statements in order to obtain 112 data. The results of this study indicate that the Operating Costs (ROA), level of capital adequacy (CAR), and Liquidity (QR) had an influence on profitability (ROA). There are also indirect influence between the level of capital adequacy (CAR) to Profitability (ROA) through Liquidity (QR), the liquidity position (QR) as the weakening of the influence.